Biogenic silver nanocomposite TFC nanofiltration membrane with antifouling properties. Issue 23 (14th May 2016) - Liu, Shasha; Zhang, Manying; Fang, Fang; Cui, Li; Wu, Junjie; Field, Robert; Zhang, Kaisong
Abstract: Biofouling is still a major obstacle hindering wider application of thin-film composite (TFC) nanofiltration membranes in the water industry. One of the practical strategies to reduce biofouling is to develop novel antibiofouling membrane materials. Well-dispersed biogenic silver nanoparticles with a diameter of ~6 nm (Bio-Ag 0 -6) were first immobilized in the selective layer of TFC nanofiltration membranes. Different dosages of Bio-Ag 0 -6 were added in the aqueous solution during the interfacial polymerization of tetraethylenepentamine and 1, 3, 5-benzenetricarbonyl trichloride (TMC). Improved properties of Bio-Ag 0 -6 /TFC membranes were systematically investigated. When the concentration of Bio-Ag 0 -6 increased from 0 to 0.05 wt.% in aqueous solution, the water flux of TFC membranes increased from 7.31 to 13.76 Lm −2  h −1 while maintaining the rejection of Na2 SO4 at a relatively high level. The addition of Bio-Ag 0 -6 also enhanced the hydrophilicity of Bio-Ag 0 -6/TFC membranes in comparison with the bare TFC membranes. All Bio-Ag 0 -6/TFC membranes exhibited an obvious antibacterial ability to inhibit the growth of Pseudomonas aeruginosa . Moreover, the Bio-Ag 0 -6/TFC membranes showed the property of a low silver leaching rate in both the static immersion and the filtration systems. It demonstrated that the embedded Bio-Ag 0 -6 in TFC membrane via interfacial polymerization improved the performance of the TFC nanofiltration membrane.